The Compiled Statutes in Force in the District of Columbia including the Acts of the Second Session of the Congress 1887-'89, William Stone Albert & Benjamin G. comps., 178 1894 (Act of July 20, 1871) - (:unkn) unknown (General Publisher, 1871)
It shall not be lawful for any person or persons to carry or have concealed about their persons any deadly or dangerous. weapons, such as daggers, air-guns, pistols, bowie-knives, dirk- knives, or dirks, razors, razor-blades, sword-canes, slung-shots, or brass or other metal knuckles, within the District of Columbia;
--
Keywords: CARRY